The Implementation of User Satisfaction Based Shortest Job First Algorithm Efficiency in Queuing System : Penerapan Efisiensi Algoritma Shortest Job First Berbasis Kepuasan Pengguna pada Sistem Antrian - Darsanto (NUANSA INFORMATIKA, 2025)
Efficient and structured queue management is crucial to ensure the smooth operation of various services in both the public and private sectors. A web-based queue system has now become a good solution due to their ease of access and ability to manage queues in real-time. In this study, a web-based queue system is developed that implements the Shortest Job First (SJF) algorithm to optimize service sequences. The SJF algorithm prioritizes services with the shortest processing duration, which is expected to reduce user waiting time and to increase overall system effectiveness. This research is conducted in the university's Bureau of General Administration and Finance queue system as the research object. The software development method uses Agile with the Extreme Programming (XP) framework. The results of system testing using the Black Box testing method to evaluate application functionality show that all test cases are valid, indicating that the system operates according to the desired requirements. System performance analysis is conducted by 40 students using the User Experience Questionnaire (UEQ), resulting in benchmark scores in which 5 variables are above average, and 1 variable is below average. These results indicate that the queue system built using the SJF algorithm is feasible and effective for users.